EFFECT OF SALT LEACHING ON SEDIMENTATION AND SELF WEIGHT CONSOLIDATION - Rondonuwu, Steeva G (TEKNO, 2017)
The soil washing treatment was carried on Ariake washed by cylinder test method, to investigate the sedimentation process and final water content change. A water-soil dilute were allowed to settling under salinity condition ranging from 30 to 2 g/L. We adjust the suspension for each sample in initial water content range from 500% to 6000%. Then let the sedimentation and self weight consolidation process occur for 14 days. After the final process, we measured the final water content and maximum settling rate. Leaching of salt decreases the liquid limit, consequently increasing the normalized water content w* defined as the ratio normal water content over liquid limit (Hong and Tsuchida.2000). They also found that the value of Iw increases lineary with the increases in w*.Â Key words: salt leaching, sedimentation, self weight consolidation, water quality, settling rate, final water content.